2016
DOI: 10.4236/aces.2016.65048
|View full text |Cite
|
Sign up to set email alerts
|

Fenton-Like Oxidation of Acid Yellow 23 in the Presence of Iron Rich Soil

Abstract: Treatment of yellow dye 23 by heterogeneous Fenton-like process was studied using iron rich soil as an iron source. The iron rich soil sample was characterized by XRD, SEM and BET analysis. XRD pattern indicates that the iron rich soil is made of goethite and hematite. The reaction was systematically investigated under various experimental conditions such as pH, iron rich soil dosage, oxidant and dye concentrations. The result revealed that using iron rich soil as catalyst led to high discoloration efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Similarly, MPC prepared from FeCl 3 /NF mass ratios of 0.05, 0.1, and 0.2 had the rate constants of 0.0138 min −1 (R 2 � 0.988), 0.0186 min −1 (R 2 � 0.993), and 0.0143 min −1 (R 2 � 0.977), respectively. Tese R 2 values from regression lines revealed that the decolorizations generally followed pseudo-frst-order kinetics, which is consistent with other earlier investigations using Febased catalysts for Fenton-like decolorization of AY23 [10,77,80].…”
Section: Kinetics Of Ay23 Decolorization With Mpc Catalystssupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, MPC prepared from FeCl 3 /NF mass ratios of 0.05, 0.1, and 0.2 had the rate constants of 0.0138 min −1 (R 2 � 0.988), 0.0186 min −1 (R 2 � 0.993), and 0.0143 min −1 (R 2 � 0.977), respectively. Tese R 2 values from regression lines revealed that the decolorizations generally followed pseudo-frst-order kinetics, which is consistent with other earlier investigations using Febased catalysts for Fenton-like decolorization of AY23 [10,77,80].…”
Section: Kinetics Of Ay23 Decolorization With Mpc Catalystssupporting
confidence: 91%
“…After 120 min of treatment, the decolorization efciencies at pH 2.0, 3.0, 3.5, 4.0, and 10.0 were 94.5, 89.1, 37.8, 24.4, and 16.5%, respectively. Although pH 2.0 ofered rapid and complete AY23 decolorization within 30 min of H 2 O 2 addition, low pH could promote Fe leaching, leading to a homogeneous mechanism for catalytic decolorization [77]. As pH increases, the interaction between AY23 molecules and the MPC surface might decrease [73].…”
Section: Efect Of Initial Phmentioning
confidence: 99%
“…The AO10 concentration almost remained constant at pH 5.0. In high pH conditions, Fe(OH) 3 can be formed from Fe(III) and cover the active sites of the catalyst, making H 2 O 2 adsorbed and reducing the amount of free •OH radicals formed [ 92 , 93 ]. Nonetheless, AO10 decolorization occurred rapidly at low pH.…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with other Fenton-like research in the literature. Although pH 2.0 offered robust and complete AY23 decolorization within 30 min of H 2 O 2 addition, low pH could promote Fe leaching, leading to a homogeneous mechanism for catalytic decolorization [ 93 ]. Overall, pH 3.0 may be appropriate for achieving a heterogeneous mechanism and maintaining high decolorization efficiency.…”
Section: Resultsmentioning
confidence: 99%